Influence of celebrity endorsement on intention to vote in presidential election in Indonesia - Ahmad Kevin Prawira; Chairy Chairy (President University, 2022)
The aim of this research specifically discusses the impact of celebrity endorsement on the intention to vote among voters in the presidential election in Indonesia. The source credibility model is adopted as the theoretical framework. In the study, the model is modified by adding variable celebrity familiarity and celebrity likeability on attitude toward celebrity endorsement and intention to vote. This study uses the quantitative method. The primary data collection technique was carried out through a survey with a questionnaire as a research instrument. The population is Indonesian citizens entitled to become voters in the 2024 presidential election. The data was collected from 140 respondents and analyzed with a partial least square (PLS)-structural equation model (SEM). The findings of this empirical study illustrate that celebrity trustworthiness, celebrity expertise, and celebrity familiarity have a significant impact on the intention to vote indirectly through attitude toward celebrity endorsement. The variable that has a more positive impact on intention to vote is celebrity familiarity compared to celebrity trustworthiness and celebrity expertise. Findings from this research are expected to enrich the literature about political marketing on the celebrity endorsement approach. The managerial implication that can be applied by politicians and campaign team is using celebrity endorser that is trusted, has the expertise, and are known well in the presidential campaign.